Automatic control system for low-loss fiber alignment in silicon photonics - Wang, Xiaolei (2017)
This report will provide an in-depth insight into my final year project experience in Nanyang Technological University and it will begin with a brief introduction of the program scope and my scope as a final year project student to enhance understanding and application of the connection between software and hardware.